Four-channel spatial multiplexing over a millimeter-wave line-of-sight link - Sheldon, C.; Munkyo Seo; Torkildson, E.; Rodwell, M.; Madhow, U. (2009 IEEE MTT-S International Microwave Symposium Digest, 2009)
A scalable system architecture is proposed and demonstrated for spatial multiplexing over millimeter-wave line-of-sight communication links. This architecture provides increased data capacity without increasing the channel bandwidth. The modulation format is simple (BPSK or QPSK); this facilitates high-rate operation. The spatially multiplexed channels are separated at the receiver using broadband adaptive analog I/Q vector signal processing, a technique which should readily scale to data rates exceeding 10 Gb/s per channel. A control loop continuously tunes the channel separation electronics to correct for changes with time in either the propagation environment or the system components. Design and characterization of a four channel 60 GHz hardware prototype is presented.